The Place of Neuro-Information Science in Defining The Information Needs of Individuals and Their Information Retrieval Process - Burcu Aydemir Şenay (Türk Kütüphaneciliği)
Due to the differences in the cognitive structures of individuals and the difference they experience in the process of adaptation to technology, users may show different search behaviors in the information retrieval process. Therefore, in this study, it has been emphasized that neural and cognitive assessment methods focused on system-user interaction can be used in the evaluation of information seeking behaviors of users in the information retrieval process.